Significance of the rdar and bdar morphotypes in the hydrophobicity and attachment to abiotic surfaces of Salmonella Sofia and other poultry-associated Salmonella serovars - Chia, T.; McMeekin, T.; Fegan, N.; Dykes, Gary (2011)
Aims: To investigate the relative role of the red dry and rough (rdar) and brown dry and rough (bdar) morphotypes on hydrophobicity and ability to attach to abiotic surfaces of poultry-associated Salmonella strains with a focus on S. Sofia. Methods and Results: Cellulose synthase gene null mutants were constructed in five Salmonella strains converting them from rdar to bdar morphotypes. One S. Sofia null mutant displayed reduced hydrophobicity and attachment to Teflon® relative to its parent strain. The S. Virchow and S. Infantis null mutants attached less well to glass relative to their parent strains. Conclusions: The rdar or bdar morphotype may influence S. Sofia persistence but did not explain why bdar strains predominate in this serotype. Significance and Impact of the Study: This work provides some insight into why some Salmonella strains survive in poultry environments and may ultimately contribute to their control.